2019
DOI: 10.1371/journal.pone.0217701
|View full text |Cite
|
Sign up to set email alerts
|

GLUcose COntrol Safety & Efficacy in type 2 DIabetes, a systematic review and NETwork meta-analysis

Abstract: Background The last international consensus on the management of type 2 diabetes (T2D) recommends SGLT-2 inhibitors or GLP-1 agonists for patients with clinical cardiovascular (CV) disease; metformin remains the first-line glucose lowering medication. Last studies suggested beneficial effects of SGLT-2 inhibitors or GLP-1 agonists compared to DPP-4 inhibitors, in secondary CV prevention. Recently, a potential benefit of SGLT-2 inhibitors in primary CV prevention also has been suggested. However, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 55 publications
(52 reference statements)
0
19
0
1
Order By: Relevance
“…Discrepancies were resolved by consensus. In line with our previous meta-analysis, 26 we used the Cochrane Collaboration’s tool for assessing risk of bias in RCTs. 28…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Discrepancies were resolved by consensus. In line with our previous meta-analysis, 26 we used the Cochrane Collaboration’s tool for assessing risk of bias in RCTs. 28…”
Section: Methodsmentioning
confidence: 99%
“…The protocol of the present review has not been registered, but the hypothesis, the bibliographic search, the outcome definition and the statistical plan were defined a priori , notably using our previous meta-analysis (which was registered in PROSPERO), 26 and the previous meta-analysis of Yang et al, specifically designed for assessing the risk of infections with DPP4 inhibitors. 5…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Los metaanálisis que evalúan drogas antidiabéticas contemporáneas en relación a mortalidad global, CV o MACE presentan datos contradictorios, sin evidencia suficiente para arribar a conclusiones [48][49][50][51][52][53][54] .…”
Section: Sulfonilureasunclassified
“…The statistical representation is done by OR=0.82 [95% CrI: 0.69; 0.98]. 19 A network meta-analysis of 171,253 participants from 91 randomized controlled trials assessing the comparative effect of these anti-diabetic agents on heart failure outcomes reported that, SGLT-2 were significantly superior to insulin (OR: 0.75, 95% CI 0.62-0.91), dipeptidyl peptidase 4 inhibitors (OR: 0.68, 95% CI 0.59-0.78), GLP-1 RA (OR: 0.65, 95% CI 0.54-0.78), and thiazolidinediones (OR: 0.46, 95% CI 0.27-0.77) in terms of heart failure risk. Furthermore, in an exploratory analysis among subjects with underlying heart failure or at risk of heart failure, the superiority of SGLT-2 was still significant.…”
Section: Cardiovascular Disease Safetymentioning
confidence: 99%